Implementing the ECOWAS Common External Tariff : Challenges and Opportunities for Nigeria - von Uexkull, Erik; Shui, Lulu (World Bank, Washington, DC, 2014)
The common external tariff (CET) for Economic Community of West African States (ECOWAS) was adopted at a Heads of State Summit in October 2013 in Dakar. This paper assesses the potential impact on Nigeria of implementing the new ECOWAS CET. It uses the World Bank's tariff reform impact simulation tool (TRIST) to simulate three scenarios: (i) keeping in place current import bans and levies which are charged in addition to tariffs, while implementing the CET tariff rate on non-banned products, (ii) removing the import bans and implementing the CET rate on all products, but keeping the additional import levies in place, and (iii) fully implementing the CET on all products and completely removing import bans and levies. The paper suggests that implementing the CET will have significant and largely positive effects on Nigerian consumers and producers. This note is intended to enrich the debate by presenting projections on the likely effects of CET implementation. To the extent possible with the limited available data, it gives a comprehensive overview of the effects to be expected on government revenue, the welfare of consumers, and the performance of Nigerian firms. It also discusses new opportunities for Nigerian firms to benefit from the regional market that are likely to arise if the CET is implemented. The note is organized as follows: section one gives introduction. Section two describes Nigeria's current trade profile with a particular focus on trade with the ECOWAS region. Section three makes use of the World Bank's TRIST to analyze the impact of implementing the CET in Nigeria in terms of changes in the level of protection by industry, government revenue from taxes levied at the border, consumer welfare, and the competitiveness of Nigerian firms. Section four shifts the focus beyond Nigeria's borders to look at the regional market within ECOWAS.